Implementation of Assessment on Recidivist Perpetrators of Narcotics Abuse at the National Narcotics Agency (BNN) of Gorontalo Province - Huru, Orpa Febrina; Beddu, Sumiyati; Nusa, Apriyanto (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to determine the implementation of assessments of recidivist perpetrators of narcotics abuse at the National Narcotics Agency (BNN) of Gorontalo Province, as well as identify supporting and inhibiting factors in the assessment process. The research method used is a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, observations, and documentation of assessment officers, addiction counselors, and recidivist perpetrators undergoing rehabilitation programs. The results of the study show that the implementation of the assessment at the Gorontalo Province BNN includes the screening stage, initial assessment, follow-up assessment, and determination of rehabilitation intervention plans. The implementation of the assessment was carried out in accordance with the Standard Operating Procedures (SOP) set by BNN, but in practice there were still obstacles such as limited human resources, lack of standardized psychological measuring tools, and low level of cooperation from recidivist actors. Nevertheless, assessment plays an important role in determining the level of dependence and the right direction of treatment for recidivists in order to reduce the risk of recurrence of narcotics abuse. Thus, increasing the capacity of officers and providing assessment support facilities are things that need to be considered for optimizing rehabilitation programs within the Gorontalo Province BNN